Creation of the mathematics syllabus in Lithuania between two world wars - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2005)
Creation of the mathematic syllabus in Lithuania between the civil and world war is presented in this article. The history syllabus is described in this period. Ideas of Kleinas and Merane program are discussed in this article.The influence and experience of foreign countries in creating the mathematics syllabus are introduced. Discussions of the first mathematics and physics conference how to improve education are presented.
Keywords: mathematics syllabus; ideas of Kleinas; Merane program; first mathematics and physics conference